Analisis Kesiapan Sumber Daya Manusia (SDM), Administrasi Dan Manajemen Pengembangan Klinik Pratama Menjadi Rumah Sakit Umum D Pratama (Studi Kasus Klinik XXX) - Daniel Ginting; Nina Fentiana (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
In the current era of BPJS, the role and existence of type D hospitals is absolutely necessary, especially in a tiered referral system for BPJS participants. This study aims to identify the readiness of human resources (HR), administration and management of the development of the XXX pratama clinic into the D Pratama General Hospital (RSU). This study uses qualitative methods with operational research. Using analysis of primary data and secondary data. The results of the study found that the XXX Pratama Clinic had started preparations for RSU D Pratama by completing the human resources according to the minimum requirements for operating RSU D Pratama. Administration and management readiness is up to standard. XXX pratama clinic to RSU D Pratama must complete human resources including at least 2 basic specialist doctors, the number of nurses is adjusted to the number of beds, pharmacists, radiographers, and analysts.